PENYEBARAN BERITA BOHONG (HOAX) SERTA DAMPAKNYA DALAM PERSPEKTIF UNDANG-UNDANG NO 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK (MAKSIGAMA, 2019)
The impact of Globalization has had the effect of increasing technological developments in Indonesia, increasing information circulating among the people. It cannot be denied that the information circulating is true or false. Hoax information is information created with the aim of spreading hatred tests. Commonly practiced by spreading slander and making news that is inversely proportional to the reality of people, products, organizations or companies that are targeted, even the political constellation of the homeland was not spared from its effects. The method used in this study is a normative juridical method. In addition, the data source used is the primary data source obtained from cases of hoax news dissemination that occurred in Indonesia, and secondary data obtained from the literature of books, journals, articles, and other literature that are used as references and complementary sources of research. The results showed Hoax according to the law is something that harms others in cyberspace and in the real world. Article 28 Paragraph 2 of Law No. 19 Year 2016 is anyone who intentionally and without the right to spread false news addressed to individuals, races, tribes, and between groups, to incite hatred and hostility will be subject to imprisonment no later than 6 (six) years and / or a maximum fine of one billion rupiah".Keywords: Hoax deployment, ITE Law